Morphology, taxonomy, and natural distribution of Brachiaria (Trin.) Griseb - Renvoize, S.A.; Clayton, W.D.; Kabuye, Christine H.S. (International Center for Tropical Agriculture, 1996)
We reviewed 97 species of the genus Brachiaria, spanning the whole taxon. The species were arranged in groups according to perceived natural affinities. The morphology of the inflorescence, especially the spikelet, was examined in detail and found to be highly variable; accordingly, the number of options for possible alliances among the species is particularly large. Although we eventually established a framework based on nine groups, their boundaries are as yet tentative, with 14 species still to be adequately grouped. The relationship of Brachiaria with other close genera is also discussed.